(3GdGbJQGM aj HjGf GdEUdGMs - (3eMeO Hf Ydj Hf hgH Hf eWjY, GHf Objb GdYjO , Jbj GdOjf GdbTjQj CHh GdaJM,J (B702 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf gPg fHP ef afhf egeI ai Ydhe GdMOjK jSJYGf HgG Ydi age eUWdMGJ Cgdg GdHGH GdChd ai CdaGX eJOGhdI JJYdb HgPg GdUfGYI s
(3BNQgG (B:s
(3Yf GHf YHGS QVi Gddg YfgeG bGd (B: (3Cf QShd Gddg Udi Gddg Ydgj hSde bHd GdQcf GdjeGfi hhVY NOg Ydjg (B) (3hGddg Gdehab HQMeJg hgh MSHfG hfYe Gdhcjd Je GdcJGH HMeO Gddg hYhfg hMSf Jhajbg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B283 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B70s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B135s
Keywords: (3GdMOjK h GdeUWdMs